2020
DOI: 10.1139/cgj-2019-0176
|View full text |Cite
|
Sign up to set email alerts
|

A microstructure-based elastoplastic model to describe the behaviour of a compacted clayey silt in isotropic and triaxial compression

Abstract: The paper focuses on the hydromechanical behaviour of an unsaturated compacted clayey silt, accounting for fabric changes induced by drying–wetting cycles occurring at low stress levels. The response along isotropic compression and triaxial compression (shear) at constant water content was investigated by laboratory tests on both as-compacted and dried–wetted samples. Compaction induces a microstructural porosity pertinent to clay peds and a macrostructural porosity external to the peds. Drying–wetting cycles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…The suction measured is found to increase even when the degree of saturation increases as the decrease in the void ratio shifted the bounding water retention curve to higher suction levels. A similar bounding effect of main water retention curves on soil behaviour under monotonic loading was observed and discussed by Tarantino & Tombalato [37] and Musso et al [26] where the shift of the main drying water retention curve resulted in the decrease in the soil suction while the degree of saturation reduced.…”
Section: (A) (B)supporting
confidence: 80%
See 1 more Smart Citation
“…The suction measured is found to increase even when the degree of saturation increases as the decrease in the void ratio shifted the bounding water retention curve to higher suction levels. A similar bounding effect of main water retention curves on soil behaviour under monotonic loading was observed and discussed by Tarantino & Tombalato [37] and Musso et al [26] where the shift of the main drying water retention curve resulted in the decrease in the soil suction while the degree of saturation reduced.…”
Section: (A) (B)supporting
confidence: 80%
“…Gallipoli et al [11] demonstrated that a decrease in the void ratio can shift soil water retention curves to higher saturation levels and vice versa. This has been reported to dictate the water retention behaviour and hence the volumetric and shear response of unsaturated soils to monotonic loading, for example in the case of a compacted clay tested under the direct shear condition [37] and a compacted silt sheared under the triaxial compression condition [26]. However, the bounding effect of soil water retention behaviour under cyclic loading has not previously been addressed mainly due to difficulties associated with the measurement of soil water retention properties during cyclic testing [16,27].…”
Section: Introductionmentioning
confidence: 99%
“…The Monte Carlo method was adopted in this section to carry out the statistical analysis of different parameters (e.g., retardation factor, degradation of contaminants, the porosity of CCL, and crack width) (Jacoboni and Reggiani 1983). The ranges of the half-width of the crack (b), the crack retardation factor (R f ), the half-life of organic contaminants in cracks (t f, 1/2 ), and the porosity of CCL (θ) was assumed to be 0-25 mm (Basnett and Brungard 1992;Xie et al 2019), 1-19 (Tang et al 1981;Yan et al 2021a), 10-90 years (Yan et al 2021a), 0.2-0.44 (Musso et al 2020), respectively. The average values of these parameters b, R f , t f,1/2 , θ are assumed to be 12.5 mm, 10, 50 years, 0.32, respectively, for the reference scenario.…”
Section: Effect Of Crack Widthmentioning
confidence: 99%
“…the void ratio of the macrostructure). The evaluation of e M should consistently consider that aggregates are the deformable 'grains' of the macrostructure [8,9], however in most works e M is simply evaluated as the ratio between the volume of voids in the macrostructure and the volume of the solids. Accordingly, the water retention curve proposed in [6] is simply obtained by subdividing the water ratio into two components: the water stored in the aggregates, quantified by the intra-aggregate water ratio e wm , and the water stored in the pores between the aggregates, quantified by the inter-aggregate water ratio e WM :…”
Section: The Retention Model For Active Clays Permeated With Distillementioning
confidence: 99%